Processing of thermally stable 3D hierarchical ZIF-8@ZnO structures and their CO2 adsorption studies - Thomas, M.; Nair, Balagopal; Anilkumar, G.; Mohamed, A.; Warrier, K.; Hareesh, U. (Elsevuer BV, 2016)
Core-shell hybrid structures of ZnO-Zeolitic Imidazolate Framework-8 (ZIF@ZnO) were obtained by the solvothermal treatment of ZnO hierarchical structures having an average cluster size of ~3 µm and surface area of ~19 m2/g. The surface area and pore volume of these supported structures could be tailored as a function of reaction time and temperature. Solvothermal treatment of ZnO structures in the presence of imidazole at 95 °C for 24 h induced extremely large surface area of 733 m2/g for the ZIF@ZnO samples. Samples thus obtained demonstrated a CO2 adsorption capacity of 0.34 mmol/g at 25 °C compared to the value of 0.052 mmol/g measured for the ZnO structures. More significantly, the ZnO core helped the ZIF-8 surface fractal assemblies to significantly improve the thermal stability and retain their near spherical shapes allowing better handling in any practical adsorption application. The results validate that surface conversion of ZnO microstructures to ZIF-8 could be an efficient pathway towards the development of ZIF based supported adsorbents for CO2 separation. © 2016 Elsevier Ltd. All rights reserved.